Legal support for the activities of self-regulating organizations (comparison of the experience of the G7 countries) - Anna F. Masalab (Правоприменение, 2019)
The subject. A number of areas of professional activity in which there is mandatory self-regulation in the Russian Federation were selected: construction (as well as engineering surveys, architectural and structural design), the activities of arbitration managers. The purpose of the article is to study the experience of foreign countries in the field of self-regulation.  The study took into account the following aspects of regulation of professional activity: features of the regulatory framework, the presence or absence of professional associations that develop standards and rules of activity, especially membership in them. In addition, the experience of regulation of medical activity as an example of the industry, which in Russia is actively discussed the feasibility of introducing mandatory self-regulation.The methodological basis for the study: general scientific methods (analysis, synthesis, comparison, description); private and academic (interpretation, formal-legal). Economically developed countries were taken, where self-regulation in certain areas have been existing for several decades: the United States, Britain, Germany, France, Italy, Japan, Canada.Results, scope. The activities of self-regulatory organizations abroad are regulated by industry legislation, a special law on self-regulatory organizations, as a rule, there is no. In contrast to the Russian practice, the emergence and further development of self-regulatory organizations abroad is not in direct connection with the emergence of mandatory legislation on mandatory membership in the self-regulating organizations. In industries with a high degree of danger to third parties (construction, medical activities), in most countries, the system of state licensing is still maintained, which deserves a positive assessment and should be taken into account by the legislator when choosing areas of activity in which state licensing should be replaced by mandatory self-regulation. In some foreign countries, representatives of consumers are included in the bodies of self-regulatory organizations along with representatives of the professional community, which deserves a positive assessment and can also be used in Russian practice.Conclusions. Two models of self-regulation are used in foreign practice: voluntary and mandatory. In the case of mandatory self-regulation in foreign countries, as a rule, there is one self-regulating organization, which has the status of a national one. It is obvious that the state control exercised over one self-regulating organization is more effective and less costly than for many of them. Therefore, the experience of foreign countries concerning the transfer of powers to a single self-regulatory organization in the case of mandatory self-regulation should be used in the Russian practice.